Polysulfone‐based anion exchange polymers for catalyst binders in alkaline electrolyzers. Issue 40 (7th July 2015) - Schauer, Jan; Žitka, Jan; Pientka, Zbyněk; Křivčík, Jan; Hnát, Jaromír; Bouzek, Karel
ABSTRACT The preparation of quaternized bisphenol A polysulfone (PSf) by chloromethylation and quaternization with trimethylamine (TMA), 1, 4‐diazabicyclo[2.2.2]octane (DABCO), 1‐methylimidazole (MI), or 1, 2‐dimethylimidazole (DMI) is described. While the ion‐exchange capacities (IECs) of MI or DMI quaternized PSf significantly decrease in concentrated KOH solutions at 60°C, the IECs of TMA or DABCO quaternized PSf are not much affected, but the membranes of these polymers become brittle. TMA quaternized PSf (IEC = 1.21 meq/g; IC = 2.45 S/m) and DABCO quaternized PSf (IEC = 1.09 meq/g; IC = 2.49 S/m) were used to bind a NiCo2O4 spinel electrocatalyst on the anode of Ni foam. Both the quaternized PSfs were quite effective in water electrolysis when used as binders, but not more effective than PTFE when rear sides of electrodes were fed with 10 wt % aqueous KOH solution. For long‐term electrolysis, binders based on more stable anion‐conductive polymers should be developed. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42581.